PESQUISA OPERACIONAL NA MINIMIZAÇÃO DE CUSTOS DE TRANSPORTE FLORESTAL - LACHINI, Edson; FIEDLER, Nilton César; SILVA, Evandro Ferreira da; VIEIRA, Giovanni Correia; SOUZA, Luandson Araújo de; CARMO, Flávio Cipriano de Assis do (Brazilian Journal of Biometrics, 2018)
This study aimed to minimize the costs of wood transportation of a forestry company by using integer linear programming. For this, we performed a detailed study about the routine of each truck by collecting information during 5 months (May to September of 2014). The proposed model in this study aimed to minimize the cost, determining the number of trips of each truck at each farm, in order to meet the company’s demand, based on information regarding at optimum load per vehicle, travel time from the farm to the industry, working days, total volume of transported wood, daily average of transported wood to the industry courtyard, average trips per day, average daily mileage, fuel consumed per day and average consumption. Were also inserted in the modeling the fixed and variable costs. The model presented satisfactory performance and consistent with the expected, in which the truck with lower production cost was the most used, with greater participation in the solution in the 3 scenarios. The proposed model has met the objectives of the work, optimizing the fleet of trucks in wood transportation from the farms to meet the demand of the factory at the lowest cost.